Comparison of the selected parameters of the anterior segment of the eye between femtosecond laser-assisted cataract surgery, microincision cataract surgery, and conventional phacoemulsification: A case-control study - Chlasta-Twardzik, Edyta (Medicine (Baltimore), 2019)
The purpose of our study was to compare the selected parameters of the anterior segment of the eye in patients after femtosecond laser-assisted cataract surgery (FLACS) with the results of microincision cataract surgery (MICS) and conventional phacoemulsification surgery (CPS). This single-center prospective randomized comparative observational study included 87 patients. Patients were randomly selected into group A (FLACS), group B (MICS) and group C (control group). All the surgeries were performed by the same experienced surgeon. Preoperative and postoperative parameters were evaluated: best-corrected visual acuity (BCVA), endothelial cell density (ECD), endothelial cell loss percentage (ECL%), central corneal thickness (CCT), central anterior and posterior corneal astigmatism induction, posterior corneal elevation map were measured. Intraoperative parameters: effective phacoemulsification time (EPT), balanced salt solution use (BSS use), total surgical time and suction time were analyzed. Examination was performed preoperatively and on the first, seventh day, one and six months postoperatively. The follow up period was 6 months. There was no statistically significant difference in BCVA, central anterior and posterior astigmatism induction between studied groups. The ECL% was statistically significant lower in the group A on the 7th day, 1 month and 6-months postoperatively (P < .05). The CCT was statistically significant lower in the group A and in the group B than in the group C on the 7th postoperative day (P = .002). However, in the 6 months follow-up there was no statistically significant difference in the CCT between studied groups (P = .133). We observed statistically significant difference in change of the posterior corneal elevation map at the periphery assessed within the 90° to 120°meridian range between group A, group B and group C at every timepoint postoperatively (P < .05). The EPT and BSS use were statistically significant lower whilst total surgery time was statistically significant higher in the FLACS group (P < .05). To conclude in the 6 months follow-up there was statistically significant difference found between eyes undergoing FLACS, MICS and CPS with respect to the posterior corneal elevation map assessed within the studied range, ECL%, EPT, BSS use and total surgery time. Postoperative BCVA, central anterior and posterior astigmatism induction, CCT were comparable between studied groups.